The development of an agent-based model to investigate possible power law relationships in peacekeeping operations - Frewer, Lorna (Engineering Systems Department, 2010)
Modelling peace support operations is a growing area of research in the defence sector. Extensive development has been done in the area of combat models but they are not always sufficient when modelling operations other than war. The DIAMOND model is a large scale peace support model capable of mod- elling entire countries. Taking an agent-based approach, we have created a model that has the potential to be used in conjunction with DIAMOND, providing the detail the larger model lacks. Improvements need to be made before this is pos- sible but our model provides a strong starting point. Self-organised criticality is an area of complexity theory that is, in part, iden- tified by a fractal frequency-size ‘avalanche’ distributions. Previous research has shown a link between self-organised criticality and combat modelling. We looked for power-law behaviour in a variety of peacekeeping scenarios. Using our agent-based model we devised a set of scenarios, each one more complex than the previous one. Taking the conflict between the peacekeepers and local insurgents, we used two different measures of such to represent the ‘avalanches’. The results showed no real evidence of power law relationships but more experimentation and analysis is needed.